Stereochemical selectivity of group II intron splicing, reverse splicing, and hydrolysis reactions. - Podar, M (1995)
We have previously shown, using phosphorothioate substitutions at splice site, that both transesterification steps of group II intron self-splicing proceed, by stereochemical inversion, with an Sp but not an Rp phosphorothioate. Under alternative reaction conditions or with various intron fragments, group II introns can splice following hydrolysis at the 5' splice site and can also hydrolyze the bond between spliced exons (the spliced-exon reopening reaction). In this study, we have determined the stereochemical specificities of all of the major model hydrolytic reactions carried out by the aI5 gamma intron from Saccharomyces cerevisiae mitochondria. For all substrates containing exon 1 and most of the intron, the stereospecificity of hydrolysis is the same as for the step 1 transesterification reaction. In contrast, the spliced-exon reopening reaction proceeds with an Rp but not an Sp phosphorothioate at the scissile bond, as does true reverse splicing. Thus, by stereochemistry, this reaction appears to be related to the reverse of step 2 of self-splicing. Finally, a substrate RNA that contains the first exon and nine nucleotides of the intron, when reacted with the intron ribozyme, releases the first exon regardless of the configuration of the phosphorothioate at the 5' splice site, suggesting that this substrate can be cleaved by either the step 1 or the step 2 reaction site. Our findings clarify the relationships of these model reactions to the transesterification reactions of the intact self-splicing system and permit new studies to be interpreted more rigorously.